Preleminary result in collecting stem cells derived from dapple deer velvet (Cervus nippon) - Băng, Nguyễn Ngọc Như; Bằng, Nguyễn Tiến; Dũng, Trần Hoàng; Hưng, Lê Thanh (Vietnam Journal of Biotechnology, 2012)
The periodic replacement of antlers is an exceptional regenerative process in mammals, which in general are unable to regenerate complete body appendages. More recent studies, however, showed that, antler regeneration is a stem - cell - based process that depends on the periodic activation of periosteal stem cells. On that basis, we tested to collect stem cells derived from dapple deer velvet The cells derived from dapple deer velvet have been collected and cultured with DMEM/F12 plus 10% FBS (fetal bovine serum). About 10th day, those cells strongly expand and cover with 70 - 80% flask’s surface. At that time, the cells derived from dapple deer velvet are subcultured by using trypsin/EDTA 0,25% to provide nutrients and surface for development. The cells derived from dapple deer velvet is multipotial like stem cells. They could be differentiated to osteocytes in DMEM/F12, 10% FBS medium plus dexamethasone, glycerol phosphate, ascorbate, acid ascorbic; to adipocytes in DMEM/F12, 10% FBS plus isobutyl - methylxanthine, dexamethasone, insulin, indomethacin.